Studi Kelayakan Usaha Budidaya Nila Salin (Oreochromis Niloticus, Linn) Secara Intensif di Kelompok Pembudidaya Ikan (Pokdakan) Perkasa Desa Karangrejo Kecamatan Manyar Kabupaten Gresik - Muawanah Muawanah; Dayang Diah; Sunanto Arifin; Putera Al Khakim Syaifullah (Journal on Education, 2022)
Salin tilapia (Oreochromis niloticus, Linn) Is a type of fish consumed in brackish water with an elongated body shape and flattened to the sides and blackish white in color. Tilapia aquaculture is a promising activity for the main actors in fisheries because the demand for tilapia is very high and tilapia aquaculture is an activity that is easy and fast to implement. The purpose of this study was to determine the feasibility of intensive saline tilapia cultivation by the Perkasa Fish Farmers Group (Pokdakan) in Karangrejo Village, Manyar Gresik District. In this study, data collection methods were used including primary data and secondary data, to calculate business feasibility, financial analysis was carried out such as operational costs, net income and BCR. The difference in variable costs is influenced by the size of the business being run. The larger the scale of the business being run, the greater the variable costs incurred. Vice versa, the smaller the business scale, the smaller the variable costs incurred. To increase income, the population size should be increased because the higher the business population, the higher the income.